(untitled) (Research, Society and Development, 2023)
Introduction: Antibiotics are drugs that have mechanisms of action that act by inhibiting or eliminating bacteria, so that when inhibiting they are called bacteriostatic and when they extinguish the microorganisms they are called bactericidal. Thus, there may be bacterial resistance to antibiotics and affect the functioning of these drugs in the body. The main objective of the article was to present in a clear and summarized way the main drivers of bacterial resistance associated with preventive measures. Methodology: In this way, 20 articles obtained by searching the Google Scholar databases using the keywords: antibiotics, bacteria and bacterial resistance were selected. The parameters for filtering the articles found include: studies carried out in Brazil and in other countries; publication dates vary between the years 2000 and 2022; publications were found both in Portuguese and in English. Result: Articles were found that addressed the causes of bacterial resistance along with preventive measures for the occurrence of these cases. Discussion: As evidenced, the indiscriminate use of antibiotics caused the antimicrobial action to be impaired, generating the development of mechanisms for the protection of bacteria, caused by spontaneous mutations and genetic recombination, which allow genetic variation and result in the development of microbial resistance. Conclusion: Thus, the importance of studying bacterial resistance and the need for measures to prevent mutations, respecting the indications and time of antibiotic use, in addition to valuing biosafety measures within hospital units, is evident.